CPEC in the Crossfire: Unraveling the Geopolitical Landscape of the China-Pakistan Economic Corridor amidst US-China Rivalry - Mudasir Hassan; Muhammad Farhan; Taimoor Zeb Khan; Sayed Idress Hashimi, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
This study explores the complex relationship between the China-Pakistan Economic Corridor (CPEC) and the growing rivalry between the United States and China. It examines how these two major global powers approach CPEC and uncovers the challenges and opportunities that arise from their competition. Employing a qualitative research methodology, this study delves into the intricate dynamics of the U.S.-China approach to CPEC. The research is grounded in the theoretical framework of Realism, providing a lens to scrutinize the nuanced interactions between these global powers. As Pakistan finds itself caught in the crossfire between the United States and China, it faces an important moment that requires a careful assessment of its future options. This study provides a detailed analysis of how this geopolitical tension affects CPEC and offers insights into the strategic decisions. The way forward for Pakistan necessitates a balanced approach, leveraging the benefits of CPEC while mitigating potential risks. Pakistan must make to protect its national interests in the midst of this global power struggle.